RISUS study: Rugby Injury Surveillance in Ulster Schools. Issue 7 (23rd December 2015) - Archbold, H A P; Rankin, A T; Webb, M; Nicholas, R; Eames, N W A; Wilson, R K; Henderson, L A; Heyes, G J; Bleakley, C M
Abstract : Objective: To examine injury patterns in adolescent rugby players and determine factors associated with injury risk. Design: Prospective injury surveillance study. Setting: N=28 Grammar Schools in Ulster, Ireland (2014–2015 playing season). Participants: 825 adolescent rugby players, across in 28 school first XV rugby squads; mean age 16.9 years. Main outcome measures: Injuries were classified by body part and diagnosis, and injury incidence using injuries per 1000 match hours of exposure. HRs for injury were calculated through Cox proportional hazard regression after correction for influential covariates. Results: A total of n=426 injuries were reported across the playing season. Over 50% of injuries occurred in the tackle situation or during collisions (270/426), with few reported during set plays. The 3 most common injury sites were head/face (n=102, 23.9%), clavicle/shoulder (n=65, 15.3%) and the knee (n=56, 13.1%). Sprain (n=133, 31.2%), concussion (n=81, 19%) and muscle injury (n=65, 15.3%) were the most common diagnoses. Injury incidence is calculated at 29.06 injuries per 1000 match hours. There were no catastrophic injuries. A large percentage of injuries (208/424) resulted in absence from play for more than 28 days. Concussion carried the most significant time out from play (n=33; 15.9%), followed by dislocations of the shoulder (n=22; 10.6%), knee sprains (n=19, 9.1%), ankle sprains (n=14, 6.7%), hand/finger/thumb (n=11; 5.3%). 36.8% of participants in the study (304/825) suffered at least one injury during the playing season. Multivariate models found higher risk of injury (adjusted HR (AHR); 95% CI) with: higher age (AHR 1.45; 1.14 to 1.83), heavier weight (AHR 1.32; 1.04 to 1.69), playing representative rugby (AHR 1.42; 1.06 to 1.90) and undertaking regular strength training (AHR 1.65; 1.11 to 2.46). Playing for a lower ranked team (AHR 0.67; 0.49 to 0.90) and wearing a mouthguard (AHR 0.70; 0.54 to 0.92) were associated with lower risk of injury. Conclusions: There was a high incidence of severe injuries, with concussion, ankle and knee ligament injuries and upper limb fractures/dislocations causing greatest time loss. Players were compliant with current graduated return-to-play regulations following concussion. Physical stature and levels of competition were important risk factors and there was limited evidence for protective equipment.